Effect of NaOH Molarity on Gel Formation at the Geopolymer–Artificial Aggregate Interface for Pavement Applications - Saputro, Yayan Adi; Adnan; Mohammad, Gunawan; Hidayati, Nor; Muna, Nando Nilna; Ningrum, Aprilia Citra (Advance Sustainable Science Engineering and Technology, 2026)
This study investigates the effect of NaOH molarity (10, 12, and 14 M) on gel formation at the geopolymer–artificial aggregate interfacial transition zone (ITZ) for sustainable pavement binder courses. The study focuses on microstructural and chemical characteristics rather than direct mechanical performance. Using XRF, FTIR, and SEM–EDX analyses, the evolution of gel phases from N-A-S-H to hybrid N/C-A-S-H at the interface was systematically characterized. Increasing NaOH molarity enhanced aluminosilicate dissolution and promoted Ca incorporation, as evidenced by the shift of the main Si–O–T band from approximately 1080 cm⁻¹ (10 M) to 960–970 cm⁻¹ (14 M) and the increase in Ca/Si ratio from 0.15 to 0.22. Among the investigated mixtures, the 12 M variant exhibited the most homogeneous and compact ITZ microstructure, characterized by a continuous reaction rim, balanced Si/Al (2.96) and Ca/Si (0.22) ratios, and minimal microcracking observed at the microscopic scale.